(untitled) (Economics and region, 2018)
Basis of evaluating social-economical security of the region independently of tools of such evaluating and forms of combining methods, algorithms and procedures of evaluating includes elementary indicators. Tools of such evaluating include fuzzy logic, method of indicators etc. Forms of combining include models and techniques. Inclusion of some indicators to aggregate of indicators for evaluating social-economical security of the region should be grounded sufficiently. Absence of rationale for forming aggregate of elementary indicators to evaluate social-economical security of the region is an outcome of absence of rules (procedures, sequence, algorithm) of their choice. Absence of rules for such choice is considered as unsolved task in existing methodical basis of evaluating. Rules for choosing elementary indicators to evaluate social-economical security of the region are considered. Such rules are the following: limited quantity of elementary indicators; quantitative (or quasi quantitative) character of indicators, calculating indicators using direct measurement or method of direct algorithms, informative capacity of every indicator. There is the sequence of selection of elementary indicators for evaluating social-economical security of the region formed in the article. Such sequence is based on defining characteristics of secure state of the region using the principle “from reverse” videlicet from impact of threats. Notion of “threat” is considered as different processes and/or phenomenon in society and economy of state and region that cause to negative compelled changes in a region that aggravate social-economical state of the region and break its social-economical development. Advisability of reduction of characteristics is considered, and it is proved that such reduction allows consistent transforming more complicated characteristic to some simple ones. Content of elementary indicators for economic component of social-economical security of the region is suggested. Such elementary indicators describe state of reduced characteristics of region secure state.